2007
DOI: 10.1007/s00114-007-0293-4
|View full text |Cite
|
Sign up to set email alerts
|

Torpor and basking in a small arid zone marsupial

Abstract: The high energetic cost associated with endothermic rewarming from torpor is widely seen as a major disadvantage of torpor. We tested the hypothesis that small arid zone marsupials, which have limited access to energy in the form of food but ample access to solar radiation, employ basking to facilitate arousal from torpor and reduce the costs of rewarming. We investigated torpor patterns and basking behaviour in free-ranging fat-tailed dunnarts Sminthopsis crassicaudata (10 g) in autumn and winter using small,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
81
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(87 citation statements)
references
References 26 publications
4
81
1
1
Order By: Relevance
“…3 predation risk or variable environmental temperatures) might also be important determinants of heterothermy in endotherms (Bieber and Ruf 2009;Mzilikazi et al 2002;Stawski and Geiser 2010;Warnecke et al 2008). Efforts have been made to generalize all factors affecting the expression of T b , whether well studied or not, into an adaptive framework (Angilletta et al 2010;Humphries et al 2003).…”
mentioning
confidence: 99%
“…3 predation risk or variable environmental temperatures) might also be important determinants of heterothermy in endotherms (Bieber and Ruf 2009;Mzilikazi et al 2002;Stawski and Geiser 2010;Warnecke et al 2008). Efforts have been made to generalize all factors affecting the expression of T b , whether well studied or not, into an adaptive framework (Angilletta et al 2010;Humphries et al 2003).…”
mentioning
confidence: 99%
“…However, basking has been observed in wild dasyurid marsupials not only during rest in the afternoon but also in the morning when animals are rewarming from torpor and therefore must remain concealed from diurnal predators (Geiser et al, 2002;Warnecke et al, 2008;Rojas et al, 2012), as would be the case for white P. sungorus on or near snow. Important in this regard is that in the past, differences in fur colour among dasyurid populations were considered to be of little importance from energetic, thermal and camouflage points of view because animals were considered to be nocturnal.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that during thermal and energetic challenges, a metabolic feedback affects the organisation of the circadian rhythm and induces diurnality in small nocturnal rodents (van der Vinne et al, 2014). For Australian carnivorous dasyurid marsupials, considered nocturnal in the past, radio-telemetry has shown that some are in fact entirely or to a large extent diurnal in winter (Warnecke et al, 2008;Körtner et al, 2010). We predict that such studies on P. sungorus in the wild will reveal not only that the species is partially diurnal but also that it uses basking near or on snow for energy conservation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By decreasing T B and metabolic rate, small animals can substantially reduce energy expenditure. Though it requires energy to arouse from torpor, some mammals can choose sites exposed to solar radiation during the day and are able to bask in sunlight, using the passive absorption of radiant heat to rewarm their body and profit from the energy saved while torpid (Warnecke et al, 2008).…”
Section: Torpormentioning
confidence: 99%